MASKED HYPERTENSION IN YOUNG PERSONS: PREVALENCE, SIGNIFICANCE OF CARDIOVASCULAR RISK FACTORS AND PROGNOSIS BY GENDER DIFFERENCES - N. P. Lyamina; A. V. Nalivaeva; V. N. Senchikhin; T. P. Lipchanskaya (Российский кардиологический журнал, 2017)
Aim. To evaluate the prevalence of masked arterial hypertension (MAH) in young persons, as the prevalence and significance of cardiovascular risk factors, taken gender differences.Material and methods. A coverage screening study of 512 young persons age 19-30 y. o. was done, from institutional workers, with no specific professional harm exposures, of those 82,4% — normotonic and 17,6% have MAH. The participants underwent clinical laboratory and instrumental investigations, 30-second breath stop test.Results. In anthropometric measures, body mass index, waist circumference, hips volume were significantly higher (p<0,005) in men and women with AHT. In men with MAH blood pressure (BP) level showed tendency to higher office systolic BP (SBP) as 130 [128;135] mmHg, than in women SBP 124 [120;130] mmHg and normotonics SBP 110 [110;120] mmHg. In men with MAH there were cardiovascular risk factors more common — smoking, dyslipidemia 6 times more prevalent than in women with MAH. The fact of inheritance predominated in MAH men (85%) comparing to MAH women (65%). In MAH the level of physical activity comparing to normotonics was 2 times lower. Men with MAH used to add table salt to their meals (57%) and ate sausages (61%), as took alcohol beverages.Conclusion. The prevalence of MAH among young males is 9,6% and 8% in young females. In young persons with MAH comparing to normotonics, cardiovascular risk factors are found more commonly, as food-related behavior disorders and target organ damage. Thirty-year risk of atherosclerotic CVD in young men with MAH was >6 times and in women >5 times higher than in normotonics of the same age.